Analysis Of The Convolutional Neural Network Method With Mobilenet Architecture In A Computer Vision-Based Industrial Waste Detection System - Tresi Aprilia; Harlinda Rasvi Nabela; Beta Arya Ash Shidik (JURNAL TEKNISI, 2026)
Abstract: Industrial waste has had a negative impact on the environment and human health. Industrial waste pollution can occur due to improperly managed waste disposal. Managing industrial waste can be one way to reduce the impact of environmental pollution. Checking industrial waste can be a solution for implementing oversight of waste management, but it will be difficult to implement if done in a large industrial area. Waste classification based on organic and non-organic waste categories. Convolutional Neural Networks (CNNs) and MobileNet can be applied to automatically detect organic and non-organic industrial waste systems. Researchers have conducted a comparative study between the Convolutional Neural Network (CNN) and MobileNet models, which is useful for obtaining the best model. The results of the analysis concluded that MobileNet has better accuracy, precision, and recall compared to the CNN model. The accuracy, precision, and recall generated by MobileNet are 99.5%, 99.4%, and 100%. Therefore, MobileNet is very suitable for implementation in an automatic industrial waste detection system in real-time applications.   Keyword: computer vision;  convolutional neural network (CNN); deep learning; industrial waste; mobilenet.  Abstrak: Limbah industri telah mengakibatkan dampak buruk bagi lingkungan dan kesehatan manusia. Pencemaran limbah industri dapat terjadi akibat pembuangan limbah yang tidak terkelola dengan baik. Pengelolaan limbah industri dapat menjadi salah satu cara untuk mengurangi dampak pencemaran lingkungan. Pengecekan limbah industri dapat menjadi solusi untuk menerapkan pengawasan terhadap pengelolaan limbah, namun akan sulit diterapkan jika dilakukan pada area industri yang luas. Klasifikasi limbah berdasarkan kategori limbah organik dan limbah non organik. Convolutional Neural Network (CNN) dan MobileNet dapat diterapkan untuk sistem pendeteksi limbah industri organik dan non organik secara otomatis. Peneliti telah melakukan studi komparatif antara model Convolutional Neural Network (CNN) dan MobileNet yang berguna untuk memperoleh model terbaik. Hasil analisa yang telah dilakukan menyimpulkan bahwasanya MobileNet mempunyai akurasi, precision dan recall yang lebih baik jika dibandingkan dengan model CNN. Akurasi, precision dan recall yang dihasilkan oleh MobileNet sebesar 99,5% 99,4% dan 100%. Oleh karena itu, MobileNet sangat cocok untuk diterapkan pada sistem deteksi limbah industri secara otomatis pada aplikasi real-time.Kata kunci: computer vision; convolutional neural network (CNN); limbah industri; mobilenet; pembelajaran mendalam.